2016
DOI: 10.5740/jaoacint.15-0261
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Assurance GDS® MPX ID for Top STEC with Reference Culture Methods for the Detection of E. coli Top 6 STEC; Direct Confirmation of Top 6 STEC from Isolation Plates and Determination of Equivalence of PickPen® and FSIS OctoMACS™ Concentration Protocols

Abstract: Assurance GDS(®) MPX ID for Top Shiga toxin-producing Escherichia coli (STEC; MPX ID) was validated according to the AOAC INTERNATIONAL Methods Committee Guidelines for Validation of Microbiological Methods for Foods and Environmental Surfaces as (1) a secondary screening method for specific detection of the Top 6 STEC serogroups (O26, O45, O103, O111, O121, and O145) in raw beef trim, raw ground beef, raw spinach, and on stainless steel; and (2) as a confirmatory method for the identification of pure culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…However, our results showed that Assurance® GDS method (using m-Ehec) and ISO/TS13136 (using BPW) allowed su cient growth of STEC to allow detection and con rmation in both vegetable and meat, with respectively 375 g and 25 g sample size tested. The results obtained with Assurance® GDS and the ISO/TS13136 method are consistent with previously for the detection of STEC serogroups in vegetables (Costa et al 2019;Feldsine et al 2016).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, our results showed that Assurance® GDS method (using m-Ehec) and ISO/TS13136 (using BPW) allowed su cient growth of STEC to allow detection and con rmation in both vegetable and meat, with respectively 375 g and 25 g sample size tested. The results obtained with Assurance® GDS and the ISO/TS13136 method are consistent with previously for the detection of STEC serogroups in vegetables (Costa et al 2019;Feldsine et al 2016).…”
Section: Discussionsupporting
confidence: 90%
“…This may result in greater di culty in isolating target bacteria from others on the agar. (2) A few authors have also described differences between serogroups isolation (Feldsine et al 2016;Fratamico et al 2011;Hallewell et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Many EHEC isolates produce this protein, including some that carry plasmids only distantly related to pO157 (Beutin et al, 1989). Accordingly, the production of enterohaemolysin can be used as a diagnostic marker of EHEC (Feldsine et al, 2016). Interestingly, enterohaemolysin is also produced by some LEE-positive, Shiga toxin-negative strains of E. coli obtained from cattle and sheep (Cookson et al, 2007).…”
Section: Dec Pathotypesmentioning
confidence: 99%